Predictive marker for response to trifluridine/tipiracil plus bevacizumab in metastatic colorectal cancer patients - Toshiaki Takahashi; Kunitoshi Shigeyasu; Yoshitaka Kondo; Sho Takeda; Hibiki Umeda; Kazuya Moriwake; Masashi Kayano; Yuya Sakurai; Shunsuke Nakamura; Masafumi Takahashi; Kaori Nitta; Kazuhiro Yoshida; et al. (BMC Cancer)
Abstract Objective Trifluridine/tipiracil (FTD/TPI) is one of the options for late-line treatment of colorectal cancer (CRC). However, the specific patient populations that would particularly benefit from it remain unclear. This study attempted to identify predictive markers of chemotherapy efficacy with trifluridine/tipiracil (FTD/TPI), focusing on the RNA-editing enzyme adenosine deaminase acting on RNA 1 (ADAR1) expression and neutrophil–lymphocyte ratio (NLR). Methods To assess the effectiveness of FTD/TPI in CRC patients, we retrospectively analyzed 72 CRC patients at Okayama University Hospital from 2014 to 2022. Results Adding bevacizumab to FTD/TPI resulted in a more prolonged progression-free survival (PFS), consistent with the SUNLIGHT study findings (p = 0.0028). Among the participants, those with a high NLR had a shorter PFS (p = 0.0395). Moreover, high ADAR1 expression was associated with longer PFS (p = 0.0151). In multivariate analysis, low ADAR1 (HR = 3.43, p = 0.01) and absence of bevacizumab (HR = 4.25, p = 0.01) were identified as factors shortening PFS. The high ADAR1 group demonstrated fewer cases of progressive disease and a higher proportion of stable disease than the low ADAR1 group (p = 0.0288). Low NLR and high ADAR1 were predictive markers of prolonged PFS in the bevacizumab-treated group (p = 0.0036). Conclusion Low NLR and high ADAR1 were predictive markers for a positive response to the FTD/TPI plus bevacizumab regimen associated with prolonged PFS. The FTD/TPI plus bevacizumab regimen should be proactively implemented in the low NLR and high ADAR1 subgroups.